Sustainable development and crime: non-statutory rape cases in Kuala Lumpur, Malaysia - Mohd Noor, Noor Azlan; Ahmad Tajudin, Bazlin Darina (2011)
Sustainable development is defined as social development that meets the needs of the present generation without compromising the ability of future generations to meet their own needs. One of the important ingredients in social development is social justice which implies no crimes or low crime rates in society. In relation to this, the Royal Malaysia Police reports that the number of rape cases in the country has been increasing tremendously for the past few years. Thus, this paper attempts to discuss rape particularly non-statutory rape with reference to Kuala Lumpur, an urbanized society in Malaysia. Non-statutory rape refers to crime committed by perpetrators on victims who are above 16 years old. This study was conducted at the Kuala Lumpur Contingent Police Headquarter (IPK, KL) involving 45 rape cases based on police reports and statements from the year 2006 to 2009. Several important findings are discovered throughout the study, of which there are certain factors that contribute to non-statutory rape. These include trust, time and location, lepak (loafing) issue, family and religious awareness. These factors need to be addressed seriously to assist social policy makers in particular, to achieve sustainable development within society. One of the vital mechanisms to be adopted is to hold community development projects to alleviate crime rates for instance, through crime awareness campaigns and others. Finally, this paper will also provide guiding principles in designing the law or policy that is more stringent and simultaneously reduce the crime. Keywords: sustainable development, social development, non-statutory rape,rape crime